Salvage stereotactic body radiotherapy (SBRT) for intraprostatic relapse after prostate cancer radiotherapy: An ESTRO ACROP Delphi consensus. (July 2021) - Jereczek-Fossa, Barbara A.; Marvaso, Giulia; Zaffaroni, Mattia; Gugliandolo, Simone Giovanni; Zerini, Dario; Corso, Federica; Gandini, Sara; Alongi, Filippo; Bossi, Alberto; Cornford, Philip; De Bari, Berardino; Fonteyne, Valérie; et al.
Highlights: Between 30% and 47% of PCa patients are at risk of intraprostatic recurrence. ADT, the standard of care, represents a serious burden in terms of QoL. Purpose of this ESTRO ACROP project is to collect experts' opinion on salvage SBRT. Low consensus was achieved, highlighting the need for further investigations. The present Delphi consensus may serve as a practical guidance for salvage SBRT. Abstract: Background and purpose: Between 30% and 47% of patients treated with definitive radiotherapy (RT) for prostate cancer are at risk of intraprostatic recurrence during follow-up. Re-irradiation with stereotactic body RT (SBRT) is emerging as a feasible and safe therapeutic option. However, no consensus or guidelines exist on this topic. The purpose of this ESTRO ACROP project is to investigate expert opinion on salvage SBRT for intraprostatic relapse after RT. Materials and Methods: A 40-item questionnaire on salvage SBRT was prepared by an internal committee and reviewed by a panel of leading radiation oncologists plus a urologist expert in prostate cancer. Following the procedure of a Delphi consensus, 3 rounds of questionnaires were sent to selected experts on prostate re-irradiation. Results: Among the 33 contacted experts, 18 (54.5%) agreed to participate. At the end of the final round, participants were able to find consensus on 14 out of 40 questions (35% overall) and major agreement on 13 questions (32.5% overall). Specifically, the consensus was reached regarding some selection criteria (no age limit, ECOG 0–1, satisfactory urinary flow), diagnostic procedures (exclusion of metastatic disease, SBRT target defined on the MRI) and therapeutic approach (no need for concomitant ADT, consideration of the first RT dose, validity of Phoenix criteria for salvage SBRT failure). Conclusion: While awaiting the results of ongoing studies, our ESTRO ACROP Delphi consensus may serve as a practical guidance for salvage SBRT. Future research should address the existing disagreements on this promising approach.